Stage-bound: feature film adaptations of Canadian and Québécois drama / André Loiselle - Loiselle, André
This acknowledgement of their dramatic origins has often led to criticism that these movies remain too rigidly anchored to the stage; too "stage-bound." Stage-Bound, the first extensive study of feature film adaptations of English Canadian and Québécois drama, challenges this reductive interpretation. André Loiselle demonstrates that theatricality is central to the meaning of these works. In the process, he reclaims these stage-bound films, which have generally been ignored by scholars.